2013
DOI: 10.1095/biolreprod.113.107730
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns and Regulatory Functions of MicroRNAs During the Initiation of Primordial Follicle Development in the Neonatal Mouse Ovary1

Abstract: The initiation of primordial follicle development is essential for female fertility, but the signals that trigger this process are poorly understood. Given the potentially important roles of microRNAs (miRNAs) in the ovary, we aimed to study the expression patterns and regulatory functions of miRNAs during the initiation of primordial follicle development. Expression patterns of miRNA in the neonatal mouse ovary were profiled by microarray, and 24 miRNAs whose abundances differed significantly between ovaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 54 publications
2
53
0
1
Order By: Relevance
“…MiR-145 has been reported to negatively regulate TGF-β signaling by directly targeting SMAD3 and TGFBR2 [19-22, 24]. We thought that this might be the mechanisms by which miR-145 inhibits TGF-β1-induced EndMT.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…MiR-145 has been reported to negatively regulate TGF-β signaling by directly targeting SMAD3 and TGFBR2 [19-22, 24]. We thought that this might be the mechanisms by which miR-145 inhibits TGF-β1-induced EndMT.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, miR-145 has been reported to directly target TGF-β receptor type 2 (TGFBR2) [23]. Downregulation of miR-145 using an antagomir caused an increase in TGFBR2 expression and activation of SMAD3 [24]. Based on these findings, we speculated that miR-145 might play a significant regulatory role in EndMT by simultaneously targeting TGFBR2 and SMAD3.…”
Section: Introductionmentioning
confidence: 98%
“…Real-time PCR was performed using the AB StepOne Plus PCR machine (Applied Biosystems, Foster City, CA, USA) as described in a previous study (37). The PCR amplification of all transcripts was performed with the gene-specific primers listed in Table 1.…”
Section: Real-time Fluorescence Quantitative Polymerase Chain Reactiomentioning
confidence: 99%
“…Yang et al (2013b) showed that 24 miRNAs are differentially expressed in mouse ovaries during the developmental period of primordial follicles into primary follicles. Whereas some miRNAs were downregulated, others were upregulated, implying they might have a role in maintaining the dormancy of primordial follicles or in initiating their development.…”
Section: Primordial To Primary Follicle Transitionmentioning
confidence: 99%
“…Whereas some miRNAs were downregulated, others were upregulated, implying they might have a role in maintaining the dormancy of primordial follicles or in initiating their development. Gene ontology analysis revealed many signaling pathways that are modulated by these differentially expressed miRNAs (Yang et al 2013b); many of these signaling pathways are involved in initiation of primordial follicle development (Skinner 2005). The upregulated miR-145 is predominantly expressed in granulosa cells of primary follicles and is undetectable in pre-granulosa cells of primordial follicles (Yang et al 2013b).…”
Section: Primordial To Primary Follicle Transitionmentioning
confidence: 99%